Difference between revisions of "2009 AIME II Problems/Problem 15"
5849206328x (talk | contribs) (→Solution 2) |
m |
||
(13 intermediate revisions by 9 users not shown) | |||
Line 4: | Line 4: | ||
== Solutions == | == Solutions == | ||
− | ===Solution 1=== | + | ===Solution 1 (Quick Calculus)=== |
+ | Let <math>V = \overline{NM} \cap \overline{AC}</math> and <math>W = \overline{NM} \cap \overline{BC}</math>. Further more let <math>\angle NMC = \alpha</math> and <math>\angle MNC = 90^\circ - \alpha</math>. Angle chasing reveals <math>\angle NBC = \angle NAC = \alpha</math> and <math>\angle MBC = \angle MAC = 90^\circ - \alpha</math>. Additionally <math>NB = \frac{4}{5}</math> and <math>AN = AM</math> by the Pythagorean Theorem. | ||
+ | |||
+ | By the Angle Bisector Formula, | ||
+ | <cmath>\frac{NV}{MV} = \frac{\sin (\alpha)}{\sin (90^\circ - \alpha)} = \tan (\alpha)</cmath> | ||
+ | <cmath>\frac{MW}{NW} = \frac{3\sin (90^\circ - \alpha)}{4\sin (\alpha)} = \frac{3}{4} \cot (\alpha)</cmath> | ||
+ | |||
+ | As <math>NV + MV =MW + NW = 1</math> we compute <math>NW = \frac{1}{1+\frac{3}{4}\cot(\alpha)}</math> and <math>MV = \frac{1}{1+\tan (\alpha)}</math>, and finally <math>VW = NW + MV - 1 = \frac{1}{1+\frac{3}{4}\cot(\alpha)} + \frac{1}{1+\tan (\alpha)} - 1</math>. Taking the derivative of <math>VW</math> with respect to <math>\alpha</math>, we arrive at | ||
+ | <cmath>VW' = \frac{7\cos^2 (\alpha) - 4}{(\sin(\alpha) + \cos(\alpha))^2(4\sin(\alpha)+3\cos(\alpha))^2}</cmath> | ||
+ | Clearly the maximum occurs when <math>\alpha = \cos^{-1}\left(\frac{2}{\sqrt{7}}\right)</math>. Plugging this back in, using the fact that <math>\tan(\cos^{-1}(x)) = \frac{\sqrt{1-x^2}}{x}</math> and <math>\cot(\cos^{-1}(x)) = \frac{x}{\sqrt{1-x^2}}</math>, we get | ||
+ | |||
+ | <math>VW = 7 - 4\sqrt{3}</math> | ||
+ | with <math>7 + 4 + 3 = \boxed{014}</math> | ||
+ | |||
+ | ~always_correct | ||
+ | |||
+ | ===Solution 2 (Projective)=== | ||
+ | Since <math>MA = \frac{\sqrt{2}}{2} \approx 0.707 > \frac{3}{5}</math>, point <math>B</math> lies between <math>M</math> and <math>A</math> on the semicircular arc. We will first compute the length of <math>\overline{AB}</math>. By the law of cosines, <math>\cos \angle MOB = \frac{-(3/5)^2 + 2(1/2)^2}{2(1/2)^2} = \frac{7}{25}</math>, so <math>\cos \angle AOB = \sin \angle MOB = \frac{24}{25}</math>. Then <math>AB^2 = 2\left(\frac{1}{2}\right)^2 - 2\left(\frac{1}{2}\right)^2 \cdot \frac{24}{25} = \frac{1}{50}</math>, so <math>AB = \frac{1}{5\sqrt{2}}</math>. | ||
+ | |||
+ | Let <math>P = AC \cap MN</math> and <math>Q = BC \cap MN</math>, and let <math>MQ = x</math>, <math>PQ = d</math>, <math>PN = y</math>. Note that<cmath>(M, P; Q, N) \stackrel{C}{=} (M, A; B, N),</cmath>that is,<cmath>\frac{QP}{QM} \div \frac{NP}{NM} = \frac{BA}{BM} \div \frac{NA}{NM}</cmath>or<cmath>\frac{d}{xy} = \frac{1/(5\sqrt{2})}{(3/5) \cdot (\sqrt{2}/2)} = \frac{1}{3}.</cmath>Hence <math>d = \frac{1}{3}xy</math>, and we also know <math>d+x+y=1</math>. Now AM-GM gives<cmath>\frac{x+y}{2} \ge \sqrt{xy} \implies \frac{1-d}{2} \ge \sqrt{3d}.</cmath>This gives the quadratic inequality <math>d^2 - 14d + 1 \ge 0</math>, which solves as<cmath>d \in \left(-\infty, 7-4\sqrt3\right] \cup \left[7+4\sqrt3, \infty\right).</cmath>But <math>d \le 1</math>, so the greatest possible value of <math>d</math> is <math>7-4\sqrt3</math>. The answer is <math>7+4+3=\boxed{014}</math>. | ||
+ | |||
+ | ~MSTang | ||
+ | |||
+ | ===Solution 3 (Calculus)=== | ||
Let <math>O</math> be the center of the circle. Define <math>\angle{MOC}=t</math>, <math>\angle{BOA}=2a</math>, and let <math>BC</math> and <math>AC</math> intersect <math>MN</math> at points <math>X</math> and <math>Y</math>, respectively. We will express the length of <math>XY</math> as a function of <math>t</math> and maximize that function in the interval <math>[0, \pi]</math>. | Let <math>O</math> be the center of the circle. Define <math>\angle{MOC}=t</math>, <math>\angle{BOA}=2a</math>, and let <math>BC</math> and <math>AC</math> intersect <math>MN</math> at points <math>X</math> and <math>Y</math>, respectively. We will express the length of <math>XY</math> as a function of <math>t</math> and maximize that function in the interval <math>[0, \pi]</math>. | ||
Line 86: | Line 109: | ||
so the maximum length of <math>XY</math> is <math>\sin(a)\times\frac{\sin(t')}{\sin(t' + a) + \cos(a)} = 7 - 4\sqrt{3}</math>, and the answer is <math>7 + 4 + 3 = \boxed{014}</math>. | so the maximum length of <math>XY</math> is <math>\sin(a)\times\frac{\sin(t')}{\sin(t' + a) + \cos(a)} = 7 - 4\sqrt{3}</math>, and the answer is <math>7 + 4 + 3 = \boxed{014}</math>. | ||
− | ===Solution | + | ===Solution 4=== |
<asy> | <asy> | ||
unitsize(144); | unitsize(144); | ||
Line 103: | Line 126: | ||
Suppose <math>\overline{AC}</math> and <math>\overline{BC}</math> intersect <math>\overline{MN}</math> at <math>D</math> and <math>E</math>, respectively, and let <math>MC = x</math> and <math>NC = y</math>. Since <math>A</math> is the midpoint of arc <math>MN</math>, <math>\overline{CA}</math> bisects <math>\angle MCN</math>, and we get | Suppose <math>\overline{AC}</math> and <math>\overline{BC}</math> intersect <math>\overline{MN}</math> at <math>D</math> and <math>E</math>, respectively, and let <math>MC = x</math> and <math>NC = y</math>. Since <math>A</math> is the midpoint of arc <math>MN</math>, <math>\overline{CA}</math> bisects <math>\angle MCN</math>, and we get | ||
<cmath>\frac{MC}{MD} = \frac{NC}{ND}\Rightarrow MD = \frac{x}{x + y}.</cmath> | <cmath>\frac{MC}{MD} = \frac{NC}{ND}\Rightarrow MD = \frac{x}{x + y}.</cmath> | ||
− | To find <math>ME</math>, we note that <math>\triangle | + | To find <math>ME</math>, we note that <math>\triangle BNE\sim\triangle MCE</math> and <math>\triangle BME\sim\triangle NCE</math>, so |
+ | |||
<cmath>\begin{align*} | <cmath>\begin{align*} | ||
\frac{BN}{NE} &= \frac{MC}{CE} \\ | \frac{BN}{NE} &= \frac{MC}{CE} \\ | ||
\frac{ME}{BM} &= \frac{CE}{NC}. | \frac{ME}{BM} &= \frac{CE}{NC}. | ||
\end{align*}</cmath> | \end{align*}</cmath> | ||
+ | |||
Writing <math>NE = 1 - ME</math>, we can substitute known values and multiply the equations to get | Writing <math>NE = 1 - ME</math>, we can substitute known values and multiply the equations to get | ||
+ | |||
<cmath>\frac{4(ME)}{3 - 3(ME)} = \frac{x}{y}\Rightarrow ME = \frac{3x}{3x + 4y}.</cmath> | <cmath>\frac{4(ME)}{3 - 3(ME)} = \frac{x}{y}\Rightarrow ME = \frac{3x}{3x + 4y}.</cmath> | ||
+ | |||
The value we wish to maximize is | The value we wish to maximize is | ||
+ | |||
<cmath>\begin{align*} | <cmath>\begin{align*} | ||
DE &= MD - ME \\ | DE &= MD - ME \\ | ||
Line 117: | Line 145: | ||
&= \frac{1}{3(x/y) + 4(y/x) + 7}. | &= \frac{1}{3(x/y) + 4(y/x) + 7}. | ||
\end{align*}</cmath> | \end{align*}</cmath> | ||
+ | |||
By the AM-GM inequality, <math>3(x/y) + 4(y/x)\geq 2\sqrt{12} = 4\sqrt{3}</math>, so | By the AM-GM inequality, <math>3(x/y) + 4(y/x)\geq 2\sqrt{12} = 4\sqrt{3}</math>, so | ||
<cmath>DE\leq \frac{1}{4\sqrt{3} + 7} = 7 - 4\sqrt{3},</cmath> | <cmath>DE\leq \frac{1}{4\sqrt{3} + 7} = 7 - 4\sqrt{3},</cmath> | ||
giving the answer of <math>7 + 4 + 3 = \boxed{014}</math>. Equality is achieved when <math>3(x/y) = 4(y/x)</math> subject to the condition <math>x^2 + y^2 = 1</math>, which occurs for <math>x = \frac{2\sqrt{7}}{7}</math> and <math>y = \frac{\sqrt{21}}{7}</math>. | giving the answer of <math>7 + 4 + 3 = \boxed{014}</math>. Equality is achieved when <math>3(x/y) = 4(y/x)</math> subject to the condition <math>x^2 + y^2 = 1</math>, which occurs for <math>x = \frac{2\sqrt{7}}{7}</math> and <math>y = \frac{\sqrt{21}}{7}</math>. | ||
+ | |||
+ | ===Solution 5 (Projective)=== | ||
+ | By Pythagoras in <math>\triangle BMN,</math> we get <math>BN=\dfrac{4}{5}.</math> | ||
+ | |||
+ | Since cross ratios are preserved upon projecting, note that <math>(M,Y;X,N)\stackrel{C}{=}(M,B;A,N).</math> By definition of a cross ratio, this becomes <cmath>\dfrac{XM}{NY}:\dfrac{NM}{NY}=\dfrac{AM}{AB}:\dfrac{MN}{NB}.</cmath> Let <math>MY=a,YX=b,XN=c</math> such that <math>a+b+c=1.</math> We know that <math>XM=a+b,XY=b,NM=1,NY=b+c,</math> so the LHS becomes <math>\dfrac{(a+b)(b+c)}{b}.</math> | ||
+ | |||
+ | In the RHS, we are given every value except for <math>AB.</math> However, Ptolemy's Theorem on <math>MBAN</math> gives <math>AB\cdot MN+AN\cdot BM=AM\cdot BN\implies AB+\dfrac{3}{5\sqrt{2}}=\dfrac{4}{5\sqrt{2}}\implies AB=\dfrac{1}{5\sqrt{2}}.</math> Substituting, we get <math>\dfrac{(a+b)(b+c)}{b}=4\implies b(a+b+c)+ac=4b, b=\dfrac{ac}{3}</math> where we use <math>a+b+c=1.</math> | ||
+ | |||
+ | Again using <math>a+b+c=1,</math> we have <math>a+b+c=1\implies a+\dfrac{ac}{3}+c=1\implies a=3\dfrac{1-c}{c+3}.</math> Then <math>b=\dfrac{ac}{3}=\dfrac{c-c^2}{c+3}.</math> Since this is a function in <math>c,</math> we differentiate WRT <math>c</math> to find its maximum. By quotient rule, it suffices to solve <cmath>(-2c+1)(c+3)-(c-c^2)=0 \implies c^2+6c-3,c=-3+2\sqrt{3}.</cmath> Substituting back yields <math>b=7-4\sqrt{3},</math> so <math>7+4+3=\boxed{014}</math> is the answer. | ||
+ | |||
+ | ~Generic_Username | ||
+ | |||
+ | |||
+ | ==Video Solution== | ||
+ | https://youtu.be/4OZyKVD05Zg?si=yg1ndnP_GperfUx6 | ||
+ | |||
+ | ~MathProblemSolvingSkills.com | ||
+ | |||
==See Also== | ==See Also== | ||
{{AIME box|year=2009|n=II|num-b=14|after=Last Problem}} | {{AIME box|year=2009|n=II|num-b=14|after=Last Problem}} | ||
+ | [[Category: Intermediate Geometry Problems]] | ||
{{MAA Notice}} | {{MAA Notice}} |
Latest revision as of 20:23, 23 May 2024
Contents
Problem
Let be a diameter of a circle with diameter 1. Let
and
be points on one of the semicircular arcs determined by
such that
is the midpoint of the semicircle and
. Point
lies on the other semicircular arc. Let
be the length of the line segment whose endpoints are the intersections of diameter
with chords
and
. The largest possible value of
can be written in the form
, where
and
are positive integers and
is not divisible by the square of any prime. Find
.
Solutions
Solution 1 (Quick Calculus)
Let and
. Further more let
and
. Angle chasing reveals
and
. Additionally
and
by the Pythagorean Theorem.
By the Angle Bisector Formula,
As we compute
and
, and finally
. Taking the derivative of
with respect to
, we arrive at
Clearly the maximum occurs when
. Plugging this back in, using the fact that
and
, we get
with
~always_correct
Solution 2 (Projective)
Since , point
lies between
and
on the semicircular arc. We will first compute the length of
. By the law of cosines,
, so
. Then
, so
.
Let and
, and let
,
,
. Note that
that is,
or
Hence
, and we also know
. Now AM-GM gives
This gives the quadratic inequality
, which solves as
But
, so the greatest possible value of
is
. The answer is
.
~MSTang
Solution 3 (Calculus)
Let be the center of the circle. Define
,
, and let
and
intersect
at points
and
, respectively. We will express the length of
as a function of
and maximize that function in the interval
.
Let be the foot of the perpendicular from
to
. We compute
as follows.
(a) By the Extended Law of Sines in triangle , we have
(b) Note that and
. Since
and
are similar right triangles, we have
, and hence,
(c) We have and
, and hence by the Law of Sines,
(d) Multiplying (a), (b), and (c), we have
,
which is a function of (and the constant
). Differentiating this with respect to
yields
,
and the numerator of this is
,
which vanishes when . Therefore, the length of
is maximized when
, where
is the value in
that satisfies
.
Note that
,
so . We compute
,
so the maximum length of is
, and the answer is
.
Solution 4
Suppose and
intersect
at
and
, respectively, and let
and
. Since
is the midpoint of arc
,
bisects
, and we get
To find
, we note that
and
, so
Writing , we can substitute known values and multiply the equations to get
The value we wish to maximize is
By the AM-GM inequality, , so
giving the answer of
. Equality is achieved when
subject to the condition
, which occurs for
and
.
Solution 5 (Projective)
By Pythagoras in we get
Since cross ratios are preserved upon projecting, note that By definition of a cross ratio, this becomes
Let
such that
We know that
so the LHS becomes
In the RHS, we are given every value except for However, Ptolemy's Theorem on
gives
Substituting, we get
where we use
Again using we have
Then
Since this is a function in
we differentiate WRT
to find its maximum. By quotient rule, it suffices to solve
Substituting back yields
so
is the answer.
~Generic_Username
Video Solution
https://youtu.be/4OZyKVD05Zg?si=yg1ndnP_GperfUx6
~MathProblemSolvingSkills.com
See Also
2009 AIME II (Problems • Answer Key • Resources) | ||
Preceded by Problem 14 |
Followed by Last Problem | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.